Alat Pengendali Stop Kontak Berbasis Wemos D1 - Hisbulloh Ahlis Munawi; Mohammad Hamzah Alwi; Ary Permatadeny Nevita; Rachmad Santoso; Elsanda Merita Indrawati (G-Tech: Jurnal Teknologi Terapan, 2023)
People in general turn on and off the power outlet still using the manual method. In addition, the current contact stock controller is only an outlet controller with 1 external port. The manufacture of this 2-port outlet control device aims to facilitate its application in household electronic equipment, namely by making an outlet control port which initially had 1 external port to 2 external ports. From the results of research and design carried out, a WEMOS D1-based socket controller has the following specifications: wemos d1 11 digital input/output pins, all pins have interrupt/pwm/12C/one-wire supported(excep DO) 1 analog input ( 3,3V max input) A micro USB connection A power jack, 9-24V power input, compatible with Arduino, compatible with nodemcu, relay 5V channel output 250VAC 30VDC 10A Module for Arduino, fiber NYAF cable, 2 holes Arde uticon socket, 16A 250V, and an iron plate as a container.